2018
DOI: 10.26442/terarkh201890114-47
|View full text |Cite
|
Sign up to set email alerts
|

The role of presepsin in the diagnosis and assessment of severity of sepsis and severe pneumonia

Abstract: The aim of this study was to evaluate marker of inflammation presepsin to improve diagnosis of severe pneumonia, sepsis. Materials and methods. 75 patients with pneumonia, sepsis, other inflammatory diseases aged from 17 to 78 years were examined. These patients have been investigated for the level of the presepsin. Presepsin level was quantified on immunohemilyuministsentny analyzer Pathfast (Mitsubishi Chemical Medience Corporation, Japan) in pg/ml. All patients had obtained an antibacterial therapy in other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Bacteria are common pathogens of community acquired pneumonia (CAP), but bacterial culture detection from blood and sputum requires several days and gives a not negligible number of false negative results [33]. In this context, plasmatic levels of PSP demonstrated a good diagnostic and prognostic value for bacterial CAP (BCAP) [16], being able to predict ICU mortality in these patients [17]. In the case of active pulmonary tuberculosis (APTB), culture basis diagnosis is not widely available, because Mycobacterium tuberculosis culturing requires specific and long-lasting culture conditions.…”
Section: Psp In Pulmonary Infectionsmentioning
confidence: 99%
“…Bacteria are common pathogens of community acquired pneumonia (CAP), but bacterial culture detection from blood and sputum requires several days and gives a not negligible number of false negative results [33]. In this context, plasmatic levels of PSP demonstrated a good diagnostic and prognostic value for bacterial CAP (BCAP) [16], being able to predict ICU mortality in these patients [17]. In the case of active pulmonary tuberculosis (APTB), culture basis diagnosis is not widely available, because Mycobacterium tuberculosis culturing requires specific and long-lasting culture conditions.…”
Section: Psp In Pulmonary Infectionsmentioning
confidence: 99%
“…The patient’s ICU unit reflects the difference in the etiology of sepsis, the more that is known about this the more specific therapies can be, so this also occupies an important part [ 38 ].Sepsis can arise from different causes, such as traumatic infection, postoperative infection, and severe pneumonia, which have different effects on the prognosis of patients [ 39 ]. These should receive recognition in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic utility of presepsin has also been evaluated in hospitalized patients with a known cause of infection. Two studies on patients with confirmed pneumonia noted an association between presepsin elevation and mortality, with presepsin elevation being more pronounced in septic patients compared to those with the relatively milder presentation of severe pneumonia [ 50 , 51 ]. Similar findings were also reported in a cohort of patients with another definite focus of infection, an enterocutaneous fistula [ 52 ].…”
Section: Reviewmentioning
confidence: 99%